Penyesalan Keputusan Konsumen Berdasarkan Faktor Rekomendasi dan Kredibilitas Informasi - Umaya, Faraz; Faturochman, Faturochman; Hadipranata, Asip F; Etseem, Magda Bhinnety (Jurnal Psikologi, 2015)
The objective of this research was to empirically examine the effects of recommendation and credibility of information on consumer’s regret over the decision regarding purchase opportunity. Post - decisional emotion was measured in terms of five aspects of consumer’s regret consisting of feeling, thought, action tendencies, actions, and emotional goal. Purchase recommendation was specified into two experimental conditions, namely recommendation and no recommendation, which signification and inaction tendencies in consumer decision making. The credibility of information was meant as a recommendation by expert and non-expert. A 2 X 2 factorial design was employed to test the hypotheses. The results demonstrated that consumer’s regret was affected by the type of recommendation and credibility of the information. The highest level of regret was observed in the subjects who received no recommendation and expert condition, followed by no recommendation and non-expert, recommendation and expert, and recommendation and non-expert. The result of analysis also revealed that the credibility of info rmation significantly influenced the types of consumer responses. This result goes with any existing consumer behavior literature, and warns marketers that strategy of giving price discount can backfire when consumer is disappointed.